Profiles of undergraduate students reading attitude - Nur Hidayanto Pancoro Setyo Putro (LITERA, 2022)
The objective of this study was to examine the profiles of undergraduate students at the English Language Education Study Program of Yogyakarta State University. One hundred and one (101) students participated in this survey research. The data were collected through a reading attitude survey adapted from McKenna’s survey. Confirmatory Factor Analysis (CFA) and Latent Profile Analysis (LPA) were the main data analyses. Results from CFA confirmed that the 25 items from the survey converged into 6 factors: attitude in academic reading in print, attitude in academic reading online, attitude in academic reading in social media, attitude in recreational reading in print, attitude in recreational reading online, and attitude in recreational reading in social media reading. Then, a 2-profile solution from LPA led to a conclusion that the students can be divided into two groups, i.e. students with positive attitude towards reading in one group and students with less positive attitude towards reading in the other group.Keywords: reading attitude, latent profile analysis, reading modeProfil sikap membaca mahasiswa S1AbstrakPenelitian ini bertujuan untuk mengetahui profil mahasiswa program sarjana pada Program Studi Pendidikan Bahasa Inggris Universitas Negeri Yogyakarta. Seratus satu (101) siswa berpartisipasi dalam penelitian survei ini. Data dikumpulkan melalui survei sikap membaca yang diadaptasi dari survei McKenna. Analisis data yang digunakan dalam penelitian ini antara lain Faktor Konfirmatori (CFA) dan Analisis Profil Laten (LPA). Hasil dari CFA menegaskan bahwa 25 item dari survei berkumpul menjadi 6 faktor: sikap dalam membaca akademik di media cetak, sikap dalam membaca akademik online, sikap dalam membaca akademik di media sosial, sikap dalam membaca rekreasi di media cetak, sikap dalam membaca rekreasi online, dan sikap dalam membaca rekreasional dalam membaca media sosial. Kemudian, solusi 2 profil dari LPA menghasilkan kesimpulan bahwa siswa dapat dibagi menjadi dua kelompok, yaitu siswa dengan sikap positif terhadap membaca dalam satu kelompok dan siswa dengan sikap kurang positif terhadap membaca di kelompok lain.Kata kunci: sikap membaca, analisis profil laten, mode membaca